3-benzyl-4-(4-methylphenyl)-1H-1,2,4-triazole-5(4H)-thione - Yildirim, SÖ; Akkurt, M; Koparir, M; Cansiz, A; Sekerci, M; Heinemann, FW (Int Union Crystallography, 2004)
The title compound, C16H15N3S, displays the usual geometrical parameters of 1,2,4-triazole derivatives. The occurrence of N-H...S hydrogen-bonding interactions results in the formation of dimers.